(untitled) (Psychology Travelogs, 2023)
The article presents the results of a theoretical analysis and an empirical study of the problem of the relationship between leadership styles and organizational trust of enterprise employees. The relevance of the problem lies in the need to rebuild the modern approach to the role of the individual specialist in the work of the organization. In the context of the research, the organization is considered as a certain space in which a person forms and reflects his psychological properties in professional activity, becomes a subject of work, and strives for professional self-realization. The tasks of the empirical study were to identify leadership styles, the level of organizational trust and their relationship among banking professionals. The results showed that more often employees of the banking sector deal with managers who use authority-subordination, less often - team management style. Indicators of the parameters that make up organizational trust indicate that most of them are in the medium range, the overall index indicates a moderate level of trust. Research on the relationship between leadership styles and the level of organizational trust has shown that: primitive leadership has an inverse relationship with trust and performance; social leadership has a direct correlation with trust and caring; authority-subordination has an inverse correlation with trust and a direct correlation with effectiveness; production-social and team leadership have a direct correlation with trust, consistency, performance and caring. Thus, from the point of view of the development of organizational trust, the optimal leadership styles are social, production-social and team, among which the most favorable is team.